Indirect effect of PM1 on endothelial cells via inducing the release of respiratory inflammatory cytokines. (June 2019) - Tian, Guoxiong; Wang, Juan; Lu, Zhongbing; Wang, Hongyun; Zhang, Wei; Ding, Wenjun; Zhang, Fang
Abstract: A large number of epidemiological studies have shown that increased cardiovascular morbidity and mortality are associated with exposure to high concentrations of PM2.5 . One of the ways that PM2.5 affects the cardiovascular system is through systemic inflammation. Inflammatory cytokines such as TNF-α, IL-1β, IL-6, and IL-8 stimulate endothelial cells, which leads to endothelial dysfunction. Compared with PM2.5, PM1 is smaller in size, has a larger surface area and absorbs more toxic substances such as heavy metals, organic compounds, and black carbon. However, the effect of PM1 on human health is less studied. Here, we used BEAS-2B cells and differentiated THP-1 cells to simulate epithelial cells and macrophages in the lung, respectively. The indirect effect of PM1 on endothelial cells was studied with a coculture model consisting of two cell lines (BEAS-2B cells and macrophages) in the top compartment and one cell line, human umbilical vein endothelial cells (EA.hy926), in the bottom compartment of a transwell plate. The results showed that PM1 could promote the release of inflammatory cytokines, including TNF-α and IL-6, from BEAS-2B cells and macrophages. In addition, PM1 upregulated ICAM-1 expression in EA.hy926 cells through TNF-α/NF-κB signaling pathways, promoting the adhesion of endothelial cells and monocytes, a key event in the initiation of atherosclerosis. Highlights: PM1 promotes the release of inflammatory cytokines from BEAS-2B cells and macrophages. PM1 -induced inflammatory cytokines activate the signaling pathways in EA.hy926 cells. PM1 regulates the expression of ICAM-1 in EA.hy926 cells through TNF-α/NF-κB signaling pathway.